Lighthouse Christmas - Buzzeo, Toni.; Carpenter, Nancy (New York : Dial Books for Young Readers, 2011)
Christmas is two days away, but Frances and her little brother Peter, who recently moved with their father to a lighthouse on an isolated island, fear that they will have no treats, no music, and no visit from Santa. Includes facts about the Flying Santa Service.
Kirkus Review
School Library Journal starred
Kirkus Review, September 2011
School Library Journal starred, October 2011
3.5
K-3.
Keywords: Brothers and sisters -- Juvenile fiction; Lighthouses -- Juvenile fiction; Brothers and sisters -- Fiction; Christmas -- Fiction; Lighthouses -- Fiction; Christmas -- Fiction; Lighthouses -- Fiction; Siblings -- Fiction; Christmas stories; Picture books for children